Clostridium perfringens in ingredients of poultry feed and control of contamination by chemical treatments - Casagrande, M. F. [UNESP]; Cardozo, M. V. [UNESP]; Beraldo-Massoli, M. C. [UNESP]; Boarini, L. [UNESP]; Longo, F. A.; Paulilo, A. C. [UNESP]; Schocken-Iturrino, R. P. [UNESP] (Poultry Science Assoc Inc, 2013)
Broiler feed can include meat and bone animal meal and vegetable meal, and one of the major contaminants of these feed components can be Clostridium perfringens. Because chemicals have the potential to inhibit the growth of this pathogen, we conducted 2 experiments to evaluate the effects of chemicals on the growth of C. perfringens in experimentally inoculated feed ingredients. In the first experiment, the objective was to verify the presence of C. perfringens in samples of ingredients. The objective of the second experiment was to evaluate the effects of Salmex, formaldehyde, and organic acids against an experimental C. perfringens inoculum. We isolated C. perfringens from 60% of the in natura samples. The treatment with 3 g/kg of Salmex, which was composed of propionic acid, formaldehyde, and terpenes, decreased the amount of C. perfringens in the samples and was more effective after the 5-d treatment. Significant differences were observed between the products and the action time, but no difference was found among the ingredients. The treatments with formaldehyde and Salmex were more efficient than the treatments with organic acid.
Keywords: Animal health; microbiology; Nutrition; poultry industry; pathogen